PARTISIPASI POLITIK PEMILIH PEMULA PADA PEMILIHAN PRESIDEN DI KECAMATAN MANDAU KABUPATEN BENGKALIS TAHUN 2014 - Rezeky Saputra; ishak " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The presidential election is one from of political participation as the embodiment of the people’s sovereignty, because at the time of the election that the people are the most important decisive for the political process in the regional by voting directly, in the selection process are voters also affect participation in determining the process presidential election. The problems of this research how do the starter voters political participation at presidential election in district saber bengklis year 2014 and what are the factors enabling and constraining political participation of voters in the presidential election in the district saber bengkalis district in 2014. This study aims to determine the from political participation of voters and determine the factors enabling and constraining political participation of voter in the presidential election in district saber Bengkalis 2014. The research approach used in this study is a qualitative approach to the type of data used primary data and secondary data obtained from the data source document and research informants. The data collection isi done by field studies such as observastion, interviews, documentation and literature and then analyzed in a descriptive way to provide an overview of the research results. The results of this study indicate that the from of participation voters in the district saber has been running well visible from its enthusiastic voters in the from of participation voting (voting), because voters in this own awareness and curiosty year to participate in determining its leader, but activities such as campaigns and join political parties still less because several factors such as the bustly of everyday life, feelings of inadequacy, and the prohibition of the family.Keywords : Political Participation, Voter starters, The Presidential Election